1831 Ind. Rev. Stat. 192, ch. 26, § 58 - (:unkn) unknown (General Publisher, 1831)
Prohibited the concealed carry of a dirk, pistol, sword-cane, or other dangerous weapon. Violators fined not exceeding one hundred dollars.
--
Keywords: CARRY - CONCEALED